Needs of Ashram for Senior Citizens A Study of Bishranti Bridra Ashram, Mulghat Dhankuta - Adhikari, Dinesh (Rupantaran: A Multidisciplinary Journal, 2023)
This research article has been prepared in the context of why the elderly need ashram. Its purpose was to emphasize the importance of ashram in solving the problems faced by senior citizen. Analyzing the key information gathered through interviews and observations, it was found that it effectively addresses the physical and spiritual needs of senior citizens.The proximity of ashrams and religious institutions has played a role in making the elderly more spiritual and peaceful. Any family home is not built only for the convenience of the elderly, but as soon as it is called an old age home, its physical structure and immaterial environment are prepared to suit the elderly. There is still a belief that those who have the children stay at their home and should not keep the elderly in ashrams. Old age Ashram is considered as a residence, care and spirituality for the elderly. It is a great option for elderly people who are helpless and want to get out of family. The old age home is becoming known as an attractive and residential place for the orphans, the bereft, the childless, the single, the deprived from basic needs and lack of family affection of elderly. Bridha Ashram is developing as a care center for the elderly in Nepal.